Complex Material and Surface Analysis of Anterolateral Distal Tibial Plate of 1.4441 Steel - Josef Hlinka; Kamila Dostalova; Katerina Peterek Dedkova; Roman Madeja; Karel Frydrysek; Jan Koutecky; Pavel Sova; Timothy E. L. Douglas (Metals, 2021)
Nickel-based austenitic stainless steels are still common for manufacture of implants intended for acute hard tissue reinforcement or stabilization, but the risk of negative reactions due to soluble nickel-rich corrosion products must be considered seriously. Corrosion processes may even be accelerated by the evolution of microstructure caused by excessive heat during machining, etc. Therefore, this study also deals with the investigation of microstructure and microhardness changes near the threaded holes of the anterolateral distal tibial plate containing approx. 14wt.% Ni by composition. There were only insignificant changes of microhardness, grain size, or microstructure orientation found close to the area of machining. In addition, wettability measurements of surface energy demonstrated only minor differences for bulk material and areas close to machining. The cyclic potentiodynamic polarization tests were performed in isotonic physiological solution. The first cycle was used for the determination of corrosion characteristics of the implant after chemical passivation, the second cycle was used to simulate real material behavior under the condition of previous surface damage by excessive pitting corrosion occurring during previous polarization. It was found that the damaged and spontaneously repassived surface showed a three-time higher standard corrosion rate than the “as received” chemically passivated surface. One may conclude that previous surface damage may decrease the lifetime of the implant significantly and increase the amount of nickel-based corrosion products distributed into surrounding tissues.